KUALIFIKASI SUNSEA RESORT MARATUA SEBAGAI RESORT BERBINTANG LIMA - Muhammad Fauzan Noor; I Wayan Lanang Nala; Jaka Fadillah (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2020)
The development of tourist destination areas requires efforts to increase the development of tourism facilities and infrastructure in the context of increasing regional income in the tourism sector. Resort as one of the supporting sectors of the tourism sector which can offer various kinds of facilities and conveniences for tourists, is certainly something that should be provided by entrepreneurs in the tourism sector, ranging from non-star types to star-rated resorts. This research was conducted at the Sunsea Resort, which is located on the Island of Maratua, Derawan Archipelago, Berau Regency, East Kalimantan. The research findings show that the Sunsea Resort has not met the standard of facilities in accordance with the Regulation of the Minister of Tourism and Creative Economy Number 53 of 2013 regarding product development, recreational facilities and other accommodation. The latest Sunsea Resort meets the standardization of three-star hotel products. Sunsea Resort is constrained by obstacles that related to accessibility, including the limited availability of logistics needs on the Island of Maratua so they have to order outside the region, the absence of cellular and internet networks, and a lack of local construction experts. So that they still have to bring in from outside the region to make efforts to develop their hotel.